Differences of Circumstance, Differences of Fact: Jefferson’s Medialist View of History - Holowchak, M. Andrew (American Studies in Scandinavia, 2015)
It is often assumed that Jefferson—acquainted with the writings of Scottish thinkers such as Adam Ferguson, Anne Robert Jacques Turgot, Lord Kames, Adam Smith, and John Millar—was a stadialist of some persuasion, as several of his writings are at least consistent with stadialism. If so, was he a cyclicalist, committed to a society having a life-cycle, or a linearist, committed to the possibility of continued convergence toward some ideal of perfection? An important letter to William Ludlow and several writings where Jefferson writes of human progress as imprescriptible suggest linear stadialism. Numerous other writings, point to urbanization as a stage of social decay, and suggest cyclicalism. The correct answer, I argue, is that Jefferson was neither a linearist nor a cyclicalist, but a medialist. He viewed movement toward increased urbanization as symptomatic of social decline, but always believed any society, by rooting itself in an agrestic manner—a normative mean between the excesses of subsistence living and urbanization—could avert decline and even work toward continued advance.